Square Peg, Round Hole: First Nations Drinking Water Infrastructure and Federal Policies, Programs, and Processes - Khosrow Farahbakhsh; Jason McCullough (International Indigenous Policy Journal, 2012)
Despite nearly a decade of targeted federal government efforts to provide potable water to First Nations communities in Canada, drinking water advisories and piped-water infrastructure gaps still persist. An indepth understanding of technical practitioners’ perspectives and experiences with federal policies, programs,and processes (PPP) may provide unique insight into the challenges behind the issues. To meet this objective, we interviewed 16 First Nations technical staff within the geopolitical boundary of the province of Ontario. Results emphasize the role played by federal government-centric principles that shape policy, and the inflexible nature of the program execution format. This study provides a foundation for understanding the policy translation process and indicates action areas to create supportive policy for First Nations drinking water service provision.